Adhesive composition and adhesive sheet
The adhesive composition, featuring (meth)acrylic acid alkyl ester monomers and a tackifying resin, addresses the challenge of maintaining adhesion and removability on diverse materials, ensuring effective label attachment and removal regardless of environmental conditions.
Patent Information
- Application Number
- JP2021021318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-12
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-02-12
AI Technical Summary
Existing adhesive compositions for attention labels struggle to maintain good adhesion and removability regardless of the material of the adherend, particularly under varying environmental conditions, such as high temperatures, without leaving adhesive residue.
An adhesive composition comprising 30% to 95% by mass of structural units derived from (meth)acrylic acid alkyl ester monomers with a biomass degree of 70% or more, 5% to 20% by mass of structural units derived from monomers with hydroxyl groups, a tackifying resin with a softening point of 80°C to 160°C, and a crosslinking agent, which forms a pressure-sensitive adhesive layer with balanced adhesiveness and removability.
The adhesive composition achieves good adhesion and excellent removability on various materials, including both highly polar and non-polar substances, even after exposure to high temperatures, without leaving residue.
Smart Images

Figure 0007599985000001 
Figure 0007599985000002 
Figure 0007599985000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet. [Background technology]
[0002] In recent years, with the growing interest in environmental issues, products using reusable organic resources derived from living organisms (also called "biomass") as raw materials have been attracting attention. In the field of adhesives, development of products using biomass raw materials has also progressed, and adhesive compositions and adhesive tapes with a high ratio of biomass raw materials, so-called high biomass degree, have been reported.
[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition that contains an acrylic pressure-sensitive adhesive containing an acrylic polymer, the acrylic polymer being a polymer of a monomer component containing more than 50% by weight of an acrylic monomer, and 50% or more of the total carbon contained in the acrylic pressure-sensitive adhesive being biomass-derived carbon. Patent Document 2 discloses an adhesive tape that contains 50 parts by mass to 150 parts by mass of a tackifier resin relative to 100 parts by mass of adhesive resin solid content, has an adhesive layer in which the temperature showing the peak value of loss tangent (tan δ) at a frequency of 1 Hz is -10°C to 50°C, and has a biomass degree of 45% or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-105308 A [Patent Document 2] JP 2020-041023 A Summary of the Invention [Problem to be solved by the invention]
[0005] 2. Description of the Related Art In recent years, retail stores such as drug stores have begun to sell products with adhesive sheets bearing advertisements such as attention labels attached thereto for the purpose of sales promotion. Products with attention labels attached are transported from the shipping source with the attention labels still attached, and are displayed and sold in retail stores. For this reason, the adhesive layer of the attention label is required to have a sufficient adhesiveness so that the label does not fall off the product during transportation and display. In addition, products with attention labels attached may be placed in a high-temperature environment during transportation. In general, attention labels are no longer needed after a product is purchased and are therefore removed from the product. For this reason, the adhesive layer of the attention label is required to be easily peeled off from the product at room temperature without leaving any adhesive residue even after being placed in a high-temperature environment, i.e., to have excellent removability.
[0006] In order to realize an adhesive layer that combines good adhesion and excellent removability, the present inventors conducted extensive research using raw materials with a high biomass ratio, specifically, (meth)acrylic acid alkyl ester monomers with a biomass ratio of 70% or more, as raw materials for the adhesive composition, and confirmed that the performance of the adhesive layer formed tends to depend on the material of the adherend. Since the materials of the adherends of attention labels (for example, the product itself and packaging materials) are diverse, it is desirable that the performance of the adhesive layer provided on the attention label is less dependent on the material of the adherend.
[0007] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition that exhibits good adhesion regardless of the material of the adherend and is capable of forming a pressure-sensitive adhesive layer that has excellent removability. The problem to be solved by another embodiment of the present disclosure is to provide a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer that exhibits good adhesion regardless of the material of the adherend and has excellent removability. [Means for solving the problem]
[0008] Specific means for solving the problems include the following aspects. <1> a (meth)acrylic copolymer containing 30% by mass to 95% by mass of structural units derived from a (meth)acrylic acid alkyl ester monomer having a biomass ratio of 70% or more, based on all structural units, and 5% by mass to 20% by mass of structural units derived from a monomer having a hydroxyl group, based on all structural units; A tackifier resin; A cross-linking agent; Including, the content of the tackifier resin is 10 parts by mass to 60 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, The pressure-sensitive adhesive composition has a content of the crosslinking agent of 0.1 to 2 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer. <2> The softening point of the tackifier resin is 80°C to 160°C. <1> The pressure-sensitive adhesive composition according to claim 1. <3> The content of the tackifier resin is 20 parts by mass to 45 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer. <1> or <2> The pressure-sensitive adhesive composition according to claim 1. <4> The (meth)acrylic copolymer does not contain any structural unit derived from a monomer having a carboxy group, or the content of the structural unit derived from a monomer having a carboxy group is in the range of more than 0% by mass to 1% by mass or less based on the total structural units. <1> ~ <3> 13. The pressure-sensitive adhesive composition according to claim 12 . <5> In the (meth)acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer having a biomass ratio of 70% or more is 4 times or more, by mass, the content of the structural unit derived from the monomer having a hydroxyl group. <1> ~ <4> 13. The pressure-sensitive adhesive composition according to claim 12 . <6> The (meth)acrylic copolymer has a biomass content of 40% or more. <1> ~ <5> 13. The pressure-sensitive adhesive composition according to claim 12 . <7> A substrate; provided on the substrate, <1> ~ <6> a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of the above items; An adhesive sheet comprising: Effect of the Invention
[0009] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer that exhibits good adhesion and excellent removability regardless of the material of an adherend. According to another embodiment of the present disclosure, there is provided a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer that exhibits good adhesion regardless of the material of the adherend and has excellent removability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The pressure-sensitive adhesive composition and pressure-sensitive adhesive sheet of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.
[0011] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0012] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when the adhesive composition contains multiple substances corresponding to each component, the amount of each component in the adhesive composition means the total amount of the multiple substances present in the adhesive composition, unless otherwise specified.
[0013] In the present disclosure, "(meth)acrylic copolymer" means a copolymer in which the content of structural units derived from monomers having a (meth)acryloyl group is 50 mass% or more of all structural units (i.e., all structural units of the (meth)acrylic copolymer).
[0014] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".
[0015] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.
[0016] In the present disclosure, "removable" means that when placed in a high temperature (e.g., 60°C) environment and then peeled off at room temperature (e.g., 23°C), the adhesive can be easily peeled off from the adherend without leaving any adhesive residue.
[0017] [Adhesive composition] The pressure-sensitive adhesive composition of the present disclosure comprises a (meth)acrylic copolymer (hereinafter also referred to as a "specific (meth)acrylic copolymer") containing 30% by mass to 95% by mass of structural units derived from a (meth)acrylic acid alkyl ester monomer (hereinafter also referred to as a "specific (meth)acrylic acid alkyl ester monomer") having a biomass degree of 70% or more, based on all structural units, and 5% by mass to 20% by mass of structural units derived from a monomer having a hydroxyl group, based on all structural units, a tackifier resin, and a crosslinking agent, wherein the content of the tackifier resin is 10 parts by mass to 60 parts by mass, based on 100 parts by mass of the specific (meth)acrylic copolymer, and the content of the crosslinking agent is 0.1 parts by mass to 2 parts by mass, based on 100 parts by mass of the specific (meth)acrylic copolymer. The pressure-sensitive adhesive composition of the present disclosure, by virtue of the above-mentioned constitution, can form a pressure-sensitive adhesive layer that exhibits good adhesion and excellent removability regardless of the material of the adherend. Also, the pressure-sensitive adhesive composition of the present disclosure, by virtue of the above-mentioned constitution, can form a pressure-sensitive adhesive layer that exhibits high holding power.
[0018] [Specific (meth)acrylic copolymer] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic copolymer [i.e., a specific (meth)acrylic copolymer] containing 30% by mass to 95% by mass of structural units derived from a (meth)acrylic acid alkyl ester monomer [i.e., a specific (meth)acrylic acid alkyl ester monomer] having a biomass degree of 70% or more, relative to all structural units, and 5% by mass to 20% by mass of structural units derived from a monomer having a hydroxyl group, relative to all structural units.
[0019] <Structural Unit Derived from Specific (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic copolymer contains 30% by mass to 95% by mass of structural units derived from a (meth)acrylic acid alkyl ester monomer having a biomass degree of 70% or more [i.e., a specific (meth)acrylic acid alkyl ester monomer] based on all structural units.
[0020] In the present disclosure, "a structural unit derived from a (meth)acrylic acid alkyl ester monomer having a biomass degree of 70% or more [i.e., a specific (meth)acrylic acid alkyl ester monomer]" means a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer having a biomass degree of 70% or more [i.e., a specific (meth)acrylic acid alkyl ester monomer].
[0021] The specific (meth)acrylic acid alkyl ester monomer is a (meth)acrylic acid alkyl ester monomer having a biomass ratio of 70% or more. In the present disclosure, the biomass degree of the specific (meth)acrylic acid alkyl ester monomer is a value measured by a method in accordance with ASTM D6866-20, and means the mass proportion of biomass-derived carbon in the total carbon contained in the specific (meth)acrylic acid alkyl ester monomer.
[0022] Specific examples of specific (meth)acrylic acid alkyl ester monomers include lauryl acrylate (LA) [biomass degree: 76.0%], lauryl methacrylate (LMA) [biomass degree: 71.4%], stearyl acrylate (SA) [biomass degree: 81.7%], myristyl acrylate [biomass degree: 78.3%], myristyl methacrylate [biomass degree: 74.1%], cetyl acrylate [biomass degree: 80.1%], cetyl methacrylate [biomass degree: 76.4%], and stearyl methacrylate [biomass degree: 78.3%]. The specific (meth)acrylic acid alkyl ester monomer is preferably at least one selected from the group consisting of lauryl acrylate (LA), lauryl methacrylate (LMA), and stearyl acrylate (SA).
[0023] The specific (meth)acrylic copolymer may contain only one type of structural unit derived from the specific (meth)acrylic acid alkyl ester monomer, or may contain two or more types.
[0024] The content of the structural units derived from the specific (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is 30% by mass to 95% by mass based on the total structural units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the specific (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is 30% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the formed adhesive layer can exhibit good adhesion not only to adherends made of highly polar materials but also to adherends made of non-polar materials. The reason for this is believed to be that the polarity of the specific (meth)acrylic acid alkyl ester monomer is low, so that the polarity of the specific (meth)acrylic copolymer is moderately low, and the polarity of the formed adhesive layer is also moderately low. From this viewpoint, the content of the structural unit derived from the specific (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is 30% by mass or more, preferably 32% by mass or more, more preferably 35% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer. The content of the structural units derived from the specific (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is 95 mass% or less, alternatively 90 mass% or less, 85 mass% or less, or 80 mass% or less, relative to the total structural units of the specific (meth)acrylic copolymer.
[0025] In the specific (meth)acrylic copolymer, the content of the structural unit derived from the specific (meth)acrylic acid alkyl ester monomer is preferably 3.5 times or more, more preferably 4 times or more, even more preferably 4.5 times or more, and particularly preferably 5 times or more, by mass, the content of the structural unit derived from the monomer having a hydroxyl group described below. When the content of the structural unit derived from the specific (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is 3.5 times or more by mass relative to the content of the structural unit derived from the monomer having a hydroxyl group, the formed adhesive layer can exhibit better adhesion not only to adherends made of highly polar materials but also to adherends made of non-polar materials. The reason for this is believed to be that the polarity of the specific (meth)acrylic copolymer is lowered due to the specific (meth)acrylic acid alkyl ester monomer having low polarity, and the polarity of the formed adhesive layer is also lowered to a more appropriate degree. In addition, the lower polarity of the specific (meth)acrylic copolymer is believed to improve the compatibility between the specific (meth)acrylic copolymer and the tackifier resin, and the effect of the tackifier resin is more fully exerted.
[0026] <Structural Unit Derived from Monomer Having a Hydroxyl Group> The specific (meth)acrylic copolymer contains 5% by mass to 20% by mass of structural units derived from monomers having a hydroxyl group based on the total structural units. The hydroxyl group of the structural unit derived from a monomer having a hydroxyl group can contribute to crosslinking with a crosslinking agent described below.
[0027] In the present disclosure, a "structural unit derived from a monomer having a hydroxyl group" refers to a structural unit formed by addition polymerization of a monomer having a hydroxyl group.
[0028] The type of the monomer having a hydroxyl group is not particularly limited. An example of a monomer having a hydroxyl group is a monomer having at least one hydroxyl group and an ethylenically unsaturated group in one molecule. The ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0029] Specific examples of monomers having a hydroxyl group include 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl (meth)acrylate. butyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. As the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl(meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and 2-hydroxyethyl acrylate (2HEA) is particularly preferred.
[0030] The specific (meth)acrylic copolymer may contain only one type of structural unit derived from a monomer having a hydroxyl group, or may contain two or more types.
[0031] The content of the structural units derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 5% by mass to 20% by mass based on the total structural units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 5% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit excellent removability regardless of the material of the adherend. In addition, when the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 5% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit high retention regardless of the material of the adherend. The reason for this is believed to be that the cohesive force of the pressure-sensitive adhesive layer formed is sufficiently high. From this viewpoint, the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 5% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, preferably 8% by mass or more, more preferably 10% by mass or more, and even more preferably 12% by mass or more. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 20% by mass or less relative to the total structural units of the specific (meth)acrylic copolymer, the formed adhesive layer can exhibit good adhesion not only to adherends made of highly polar materials but also to adherends made of non-polar materials. The reason for this is considered to be that the polarity of the specific (meth)acrylic copolymer is not excessively high, so that the compatibility between the specific (meth)acrylic copolymer and the tackifier resin is good, and the effect of the tackifier resin is fully exerted. In addition, the polarity of the specific (meth)acrylic copolymer is not excessively high, so that the polarity of the formed adhesive layer is not excessively high. From this viewpoint, the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 20% by mass or less, preferably 18% by mass or less, more preferably 16% by mass or less relative to the total structural units of the specific (meth)acrylic copolymer.
[0032] <Structural Unit Derived from Monomer Having a Carboxy Group> The specific (meth)acrylic copolymer preferably does not contain any structural units derived from a monomer having a carboxy group, or the content of structural units derived from a monomer having a carboxy group is in the range of more than 0% by mass and not more than 1% by mass relative to all structural units, more preferably does not contain any structural units derived from a monomer having a carboxy group, or the content of structural units derived from a monomer having a carboxy group is in the range of more than 0% by mass and not more than 0.5% by mass relative to all structural units, even more preferably does not contain any structural units derived from a monomer having a carboxy group, or the content of structural units derived from a monomer having a carboxy group is in the range of more than 0% by mass and not more than 0.1% by mass relative to all structural units, and particularly preferably does not contain any structural units derived from a monomer having a carboxy group. When the specific (meth)acrylic copolymer does not contain a constituent unit derived from a monomer having a carboxyl group, or the content of the constituent unit derived from a monomer having a carboxyl group is in the range of more than 0 mass% to 1 mass% or less with respect to the total constituent units, the pressure-sensitive adhesive layer formed can exhibit better removability from an adherend made of a highly polar material.The reason for this is believed to be that excessive adhesion to the adherend made of a highly polar material can be suppressed.
[0033] In the present disclosure, a "structural unit derived from a monomer having a carboxy group" refers to a structural unit formed by addition polymerization of a monomer having a carboxy group.
[0034] The type of the monomer having a carboxy group is not particularly limited. An example of a monomer having a carboxy group is a monomer having at least one carboxy group and an ethylenically unsaturated group in one molecule. The ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group.
[0035] Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,Ma Examples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate.
[0036] <Other structural units derived from (meth)acrylic acid alkyl ester monomers> The specific (meth)acrylic copolymer may contain a structural unit derived from a (meth)acrylic acid alkyl ester monomer other than the specific (meth)acrylic acid alkyl ester monomer (so-called other (meth)acrylic acid alkyl ester monomer). The other structural units derived from alkyl (meth)acrylate monomers can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.
[0037] In the present disclosure, the term "structural units derived from other (meth)acrylic acid alkyl ester monomers" refers to structural units formed by addition polymerization of other (meth)acrylic acid alkyl ester monomers. The "other (meth)acrylic acid alkyl ester monomers" in the present disclosure does not include monomers corresponding to the above-mentioned monomers having a hydroxyl group and monomers corresponding to the above-mentioned monomers having a carboxy group.
[0038] The type of the other (meth)acrylic acid alkyl ester monomer is not particularly limited. The other (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the other (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.
[0039] Other specific examples of (meth)acrylic acid alkyl ester monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. As the other (meth)acrylic acid alkyl ester monomer, for example, n-butyl acrylate (n-BA) is preferable.
[0040] When the specific (meth)acrylic copolymer contains a structural unit derived from another (meth)acrylic acid alkyl ester monomer, the specific (meth)acrylic copolymer may contain only one type of structural unit derived from the other (meth)acrylic acid alkyl ester monomer, or may contain two or more types of structural units derived from the other (meth)acrylic acid alkyl ester monomer.
[0041] When the specific (meth)acrylic copolymer contains a constituent unit derived from another (meth)acrylic acid alkyl ester monomer, the content of the constituent unit derived from the other (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is not particularly limited, but is, for example, preferably 5% by mass to 65% by mass, more preferably 5% by mass to 50% by mass, even more preferably 5% by mass to 30% by mass, and particularly preferably 5% by mass to 20% by mass, relative to all constituent units of the specific (meth)acrylic copolymer.
[0042] <Other building blocks> The specific (meth)acrylic copolymer may contain structural units (so-called other structural units) other than the above-mentioned structural units, i.e., the structural units derived from the specific (meth)acrylic acid alkyl ester monomer and the structural units derived from monomers having a hydroxyl group, which are essential structural units, and the structural units derived from monomers having a carboxy group, which are optional structural units, and the structural units derived from other (meth)acrylic acid alkyl ester monomers, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0043] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.
[0044] When the specific (meth)acrylic copolymer contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0045] When the specific (meth)acrylic copolymer contains other structural units, the content of the other structural units in the specific (meth)acrylic copolymer is not particularly limited and can be appropriately set depending on the purpose within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0046] <<Weight average molecular weight of specific (meth)acrylic copolymer>> The weight average molecular weight (hereinafter also referred to as "Mw") of the specific (meth)acrylic copolymer is not particularly limited, but is, for example, preferably 300,000 to 2,000,000, more preferably 400,000 to 1,800,000, even more preferably 450,000 to 1,500,000, and particularly preferably 500,000 to 1,000,000. When the weight average molecular weight of the specific (meth)acrylic copolymer is 300,000 or more, the tackiness of the pressure-sensitive adhesive layer is reduced, and the pressure-sensitive adhesive sheet tends to have better processability when cut. When the weight average molecular weight of the specific (meth)acrylic copolymer is 2,000,000 or less, the viscosity of the pressure-sensitive adhesive composition does not increase excessively, and the pressure-sensitive adhesive composition tends to have better coatability.
[0047] The weight average molecular weight of the specific (meth)acrylic copolymer is a value measured by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic copolymer is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic copolymer. (2) Using the film-like specific (meth)acrylic copolymer obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic copolymer in the sample solution. (3) Using gel permeation chromatography (GPC), the weight average molecular weight of the specific (meth)acrylic copolymer is measured in terms of standard polystyrene under the following conditions.
[0048] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min
[0049] The weight average molecular weight of the specific (meth)acrylic copolymer can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, and the like.
[0050] <<Biomass content of specific (meth)acrylic copolymers>> The biomass ratio of the specific (meth)acrylic copolymer is not particularly limited, but from the viewpoint of consideration of environmental issues, it is preferably 25% or more, more preferably 30% or more, even more preferably 35% or more, and particularly preferably 40% or more. The upper limit of the biomass degree of the specific (meth)acrylic copolymer is not particularly limited, but may be, for example, 75% or less.
[0051] The biomass degree of a specific (meth)acrylic copolymer is a value measured by a method in accordance with ASTM D6866-20, and means the mass proportion of biomass-derived carbon in the total carbon contained in the (meth)acrylic copolymer.
[0052] <<Content of specific (meth)acrylic copolymer>> The content of the specific (meth)acrylic copolymer in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 60% by mass to 91% by mass, more preferably 64% by mass to 87% by mass, even more preferably 66% by mass to 84% by mass, and particularly preferably 68% by mass to 80% by mass, relative to the total solid content in the pressure-sensitive adhesive composition.
[0053] In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.
[0054] [Method for producing specific (meth)acrylic polymer] The method for producing the specific (meth)acrylic copolymer is not particularly limited. The specific (meth)acrylic copolymer can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.
[0055] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and the mixture is heated and reacted for several hours with stirring at the reflux temperature of the organic solvent. In this case, at least a part of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively. The reaction may also be carried out in a nitrogen gas flow.
[0056] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0057] In producing the specific (meth)acrylic copolymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic copolymer, the ease of the polymerization reaction, and the like.
[0058] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.
[0059] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic copolymer, it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.
[0060] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.
[0061] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0062] In producing the specific (meth)acrylic copolymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.
[0063] When a chain transfer agent is used in producing the specific (meth)acrylic copolymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0064] The polymerization temperature is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0065] [Tackifier resin] The pressure-sensitive adhesive composition of the present disclosure contains a tackifier resin. The content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass to 60 parts by mass relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0066] In the present disclosure, the term "tackifier resin" refers to a polymer that has the property of being able to impart tackiness when blended and has a molecular weight of less than 10,000 (preferably in the range of 500 or more and less than 10,000).
[0067] The molecular weight of the tackifier resin is a value measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic copolymer described above. However, when a commercially available product is used as the tackifier resin and the molecular weight is listed in the catalog of the commercially available product, the molecular weight of the tackifier resin is taken from the value in the catalog of the commercially available product.
[0068] The type of tackifier resin is not particularly limited. The tackifier resin is preferably a plant-derived tackifier resin. Tackifying resins include, for example, terpene resins, rosin resins, and styrene resins. The tackifier resin is preferably at least one selected from the group consisting of terpene resins and rosin resins.
[0069] Examples of terpene resins include polyterpenes which are homopolymers of terpene, terpene phenol resins, aromatic modified terpene resins, and hydrogenated terpene resins. The terpene resin is preferably at least one selected from polyterpene and terpene phenol resins. The terpene phenol resin is a copolymer of a terpene compound and a phenol compound. Specific examples of terpene phenol resins include copolymers of monocyclic monoterpene compounds such as α-pinene, β-pinene, and dipentene (limonene) with phenol compounds such as phenol, cresol, and bisphenol A.
[0070] Examples of rosin resins include rosin, esterified rosin (so-called rosin ester resin), hydrogenated rosin, and disproportionated rosin. The rosin resin is preferably a rosin ester resin.
[0071] The softening point of the tackifier resin is not particularly limited, but is, for example, preferably 30°C to 160°C, more preferably 60°C to 160°C, even more preferably 80°C to 160°C, and particularly preferably 100°C to 160°C. When the softening point of the tackifier resin is 30° C. or higher, the pressure-sensitive adhesive layer formed tends to exhibit better removability regardless of the material of the adherend. When the softening point of the tackifier resin is 160° C. or lower, the tackifier resin tends to be easily available.
[0072] The softening point of the tackifier resin is a value measured by a method in accordance with JIS K 7234:1986 (the so-called ring and ball method). However, when a commercially available product is used as the tackifier resin and the softening point is listed in the catalog of the commercially available product, the softening point of the tackifier resin is taken from the value in the catalog of the commercially available product.
[0073] As the tackifier resin, commercially available products can be used. Examples of commercially available tackifier resins include, for example, "YS Polystar (registered trademark) U115", "YS Polystar (registered trademark) U130", "YS Polystar (registered trademark) T30", "YS Polystar (registered trademark) T80", "YS Polystar (registered trademark) T100", "YS Polystar (registered trademark) T115", "YS Polystar (registered trademark) T130", "YS Polystar (registered trademark) TH130", "YS Polystar (registered trademark) T145", "YS Polystar (registered trademark) T160", "YS Polystar (registered trademark) S145", "YS Polystar (registered trademark) G125", "YS Polystar (registered trademark) G150", "YS Polystar (registered trademark) N125", "YS Polystar (registered trademark) K125", "YS Polystar (registered trademark) K140", "YS Resin (registered trademark) CP", "YS Resin (registered trademark) PX800", and "YS Resin (registered trademark) Examples of such resins include "PX1000", "YS Resin (registered trademark) PX1150", "YS Resin (registered trademark) PX1250", "YS Resin (registered trademark) TO85", "YS Resin (registered trademark) TO105", "YS Resin (registered trademark) TO115", and "YS Resin (registered trademark) TO125" manufactured by Arakawa Chemical Industries, Ltd., "Pine Crystal (registered trademark) KE-359", "Pine Crystal (registered trademark) D-6011", "Super Ester A-100", "Tamanol (registered trademark) 803L", and "Tamanol (registered trademark) 901" manufactured by Kraton Corporation, and "SYLVALITE (registered trademark) 9000" (all of the above are product names).
[0074] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of tackifier resin, or may contain two or more types.
[0075] The content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass to 60 parts by mass relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit good adhesion regardless of the material of the adherend. This is thought to be because the pressure-sensitive adhesive layer formed is given appropriate adhesion to the adherend. From this viewpoint, the content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 25 parts by mass or more. When the content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 60 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit excellent removability regardless of the material of the adherend. This is thought to be because the pressure-sensitive adhesive layer formed does not adhere excessively to the adherend. From this viewpoint, the content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is 60 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, preferably 55 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 45 parts by mass or less. Furthermore, when the content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure is within the above range relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit high holding power regardless of the material of the adherend, presumably because an appropriate cohesive force is imparted to the pressure-sensitive adhesive layer formed. The content of the tackifier resin in the pressure-sensitive adhesive composition of the present disclosure may be, for example, 20 parts by mass to 50 parts by mass, 20 parts by mass to 45 parts by mass, or 25 parts by mass to 45 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic copolymer.
[0076] [Crosslinking Agent] The pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent. The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 2 parts by mass relative to 100 parts by mass of the above-mentioned specific (meth)acrylic copolymer.
[0077] The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent.
[0078] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.
[0079] As the crosslinking agent, an isocyanate-based crosslinking agent is preferred. The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.
[0080] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).
[0081] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of crosslinking agent, or may contain two or more types.
[0082] The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 2 parts by mass with respect to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit excellent removability regardless of the material of the adherend. When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit high retention regardless of the material of the adherend. This is considered to be because the cohesive force of the pressure-sensitive adhesive layer formed is sufficiently high. From this viewpoint, the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, preferably 0.2 parts by mass or more, and more preferably 0.3 parts by mass or more. When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 2 parts by mass or less per 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed can exhibit good adhesion regardless of the material of the adherend. This is thought to be because the pressure-sensitive adhesive layer formed is given appropriate adhesion to the adherend. From this viewpoint, the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 2 parts by mass or less, preferably 1.5 parts by mass or less, and more preferably 1 part by mass or less per 100 parts by mass of the specific (meth)acrylic copolymer.
[0083] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be improved. As the organic solvent, for example, the same organic solvent as that used in the polymerization reaction of the specific (meth)acrylic copolymer can be used.
[0084] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.
[0085] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be appropriately set depending on the purpose.
[0086] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the specific (meth)acrylic copolymer, crosslinking catalysts, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.
[0087] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components can be appropriately set within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0088] <Biomass Degree of Pressure-Sensitive Adhesive Composition> The biomass degree of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but from the viewpoint of consideration of environmental issues, it is preferably 40% or more, more preferably 45% or more, even more preferably 50% or more, and particularly preferably 55% or more. The upper limit of the biomass degree of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but may be, for example, 80% or less.
[0089] The biomass degree of the pressure-sensitive adhesive composition of the present disclosure is a value measured by a method in accordance with ASTM D6866-20, and means the mass proportion of biomass-derived carbon to the total carbon contained in the pressure-sensitive adhesive composition.
[0090] <Application> The application of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited. The pressure-sensitive adhesive composition of the present disclosure exhibits good adhesion regardless of the material of the adherend, and is capable of forming a pressure-sensitive adhesive layer with excellent removability, making it suitable for use in, for example, attention labels. In addition, the adhesive composition of the present disclosure can form an adhesive layer that exhibits high retention regardless of the material of the adherend. It is desirable that the adhesive layer of the attention label exhibits high retention so that the attention label does not shift from its initial position or does not fall off the product unexpectedly. For example, if the attention label shifts position after being attached, the adhesive layer may protrude from the attention label and adhere to other products. The adhesive composition of the present disclosure is suitable for attention labels in that it can form an adhesive layer that exhibits high retention in addition to good adhesion and excellent removability.
[0091] The pressure-sensitive adhesive composition of the present disclosure can be used regardless of the material of the adherend. For example, the pressure-sensitive adhesive composition of the present disclosure can be preferably used for adherends made of either highly polar or non-polar materials. Specific examples of highly polar materials include metals such as stainless steel (SUS), aluminum, and copper, resins such as acrylic resins and polycarbonate resins, and glass. Specific examples of non-polar materials include polyolefin resins (eg, polyethylene (PE) and polypropylene (PP)), styrene resins, and the like.
[0092] [Adhesive sheet] The pressure-sensitive adhesive sheet of the present disclosure includes a substrate and a pressure-sensitive adhesive layer provided on the substrate and formed from the pressure-sensitive adhesive composition of the present disclosure, that is, in the pressure-sensitive adhesive sheet of the present disclosure, the substrate and the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure are laminated together. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present disclosure exhibits good adhesion and excellent removability regardless of the material of the adherend. In addition, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present disclosure exhibits high holding power regardless of the material of the adherend. The adhesive sheet of the present disclosure will not accidentally peel off or shift from its affixed position after being attached to an adherend, and can be easily peeled off from the adherend when it is no longer needed, making it suitable, for example, as an attention label. Furthermore, the pressure-sensitive adhesive sheet of the present disclosure can be used regardless of the material of the adherend. For example, the pressure-sensitive adhesive sheet of the present disclosure can be preferably used for adherends made of both highly polar and non-polar materials.
[0093] The substrate is not particularly limited as long as a pressure-sensitive adhesive layer can be formed on the substrate. Examples of the substrate include films containing resins such as polyolefin resins (e.g., polyethylene (PE) and polypropylene (PP)), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.
[0094] The surface of the substrate on which the adhesive layer is provided may be subjected to a surface treatment such as corona discharge treatment or plasma discharge treatment (so-called adhesion enhancing treatment) in order to improve adhesion between the substrate and the adhesive layer.
[0095] The substrate may contain various additives, such as plasticizers, colorants (eg, dyes and pigments), heat stabilizers, light stabilizers, antistatic agents, flame retardants, antioxidants, and the like. The substrate may be partially or entirely patterned.
[0096] The thickness of the substrate is not particularly limited, but is generally 10 μm to 500 μm, preferably 10 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 10 μm to 100 μm.
[0097] "Substrate thickness" in this disclosure means the average thickness of the substrate. The average thickness of the substrate is a value measured by the following method. The arithmetic mean value of the thicknesses of the substrate measured at 10 randomly selected points in the thickness direction of the substrate is calculated, and the obtained value is regarded as the average thickness of the substrate. The thickness of the substrate is measured using a film thickness meter.
[0098] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is generally 1 μm to 100 μm, preferably 5 μm to 50 μm, more preferably 10 μm to 45 μm, and even more preferably 15 μm to 40 μm.
[0099] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by a method conforming to the above-mentioned method for measuring the average thickness of the substrate.
[0100] In the pressure-sensitive adhesive sheet of the present disclosure, the exposed surface of the pressure-sensitive adhesive layer may be protected by a release film.
[0101] The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive sheet is put to practical use, and is peeled off at the time of use.
[0102] [How to make adhesive sheets] The method for producing the pressure-sensitive adhesive sheet of the present disclosure is not particularly limited. The pressure-sensitive adhesive sheet of the present disclosure can be produced by known methods. The pressure-sensitive adhesive sheet of the present disclosure can be produced, for example, by the following method. The adhesive composition of the present disclosure is applied to the easy-adhesion treated surface of the substrate to form a coating film on the substrate. The formed coating film is then dried to form an adhesive film on the substrate. The exposed surface of the formed adhesive film is then laminated to the easy-release treated surface of a release film, and then cured to produce an adhesive sheet having a laminated structure of substrate / adhesive layer / release film.
[0103] As another method, for example, the following method can be mentioned. The pressure-sensitive adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then laminated to the easy-adhesion treated surface of a substrate, and then cured to produce an adhesive sheet having a laminated structure of substrate / adhesive layer / release film.
[0104] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.
[0105] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.
[0106] The curing is carried out, for example, for 4 to 7 days in an environment with an atmospheric temperature of 20° C. to 35° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH). EXAMPLES
[0107] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.
[0108] [Production of (meth)acrylic copolymer] [Manufacturing example A-1] A reactor equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 312 parts by mass of ethyl acetate (organic solvent for polymerization) and 0.07 parts by mass of 2,2'-azobisisobutyronitrile (AIBN; polymerization initiator). In another vessel, 600 parts by mass of a monomer mixture consisting of 450 parts by mass of lauryl acrylate (LA) (biomass degree: 76.0%, specific (meth)acrylic acid alkyl ester monomer), 60 parts by mass of n-butyl acrylate (n-BA) (biomass degree: 0%, other (meth)acrylic acid alkyl ester monomer), and 90 parts by mass of 2-hydroxyethyl acrylate (2HEA) (biomass degree: 0%, monomer having a hydroxyl group) was prepared. 150 parts by mass (corresponding to 25% by mass of the monomer mixture) of the prepared monomer mixture was charged into the reactor, and then heated and refluxed at reflux temperature for 20 minutes. Next, under reflux temperature conditions, the remaining 450 parts by mass of the monomer mixture (corresponding to 75% by mass of the monomer mixture), 100 parts by mass of ethyl acetate [organic solvent for polymerization], and 0.20 parts by mass of AIBN (polymerization initiator) were successively dropped into the reaction apparatus over a period of 90 minutes, and the reaction was maintained for 90 minutes after the completion of the dropping to carry out polymerization reaction A. Into the reaction apparatus in which the polymerization reaction A was carried out, 60 parts by mass of ethyl acetate [organic solvent for polymerization] and 0.56 parts by mass of AIBN [polymerization initiator] were successively dropped over a period of 30 minutes, and after completion of the dropping, the reaction mixture was maintained for 150 minutes to carry out the polymerization reaction B. The solution after carrying out the polymerization reaction B was diluted with toluene [organic solvent] so that the solid content concentration became 46% by mass, thereby obtaining a solution of a (meth)acrylic copolymer A-1.
[0109] The term "solid content concentration" used herein means the mass proportion of the (meth)acrylic copolymer A-1 in the solution of the (meth)acrylic copolymer A-1. The same applies to each of the solutions of the following (meth)acrylic copolymers A-2 to A-11.
[0110] [Manufacturing examples A-2 to A-11] In Production Examples A-2 to A-11, the monomer composition of the (meth)acrylic copolymer was changed to the monomer composition shown in Table 1, and the weight average molecular weight of the (meth)acrylic copolymer was adjusted to the weight average molecular weight shown in Table 1 by adjusting at least one of the amount of organic solvent used and the amount of polymerization initiator used. Except for this, the same operation as in Production Example A-1 was performed to obtain solutions of (meth)acrylic copolymers A-2 to A-11 each having a solid content concentration of 46 mass%.
[0111] Table 1 shows the monomer compositions (unit: mass%) of the (meth)acrylic copolymers A-1 to A-11, the weight average molecular weights (Mw) of the (meth)acrylic copolymers A-1 to A-11, the biomass degrees (unit: %) of the (meth)acrylic copolymers A-1 to A-11, and the mass ratios [(A) / (B)] of the (meth)acrylic copolymers A-1 to A-11. In Table 1, for the sake of convenience, monomers corresponding to specific (meth)acrylic acid alkyl ester monomers, monomers having a hydroxyl group, other (meth)acrylic acid alkyl ester monomers, and monomers having a carboxy group are classified and labeled as "(A)," "(B)," "(C)," and "(D)," respectively. In Table 1, "BM" in the monomer composition column means biomass degree.
[0112] The biomass degree of the specific (meth)acrylic acid alkyl ester monomer, the monomer having a hydroxyl group, the other (meth)acrylic acid alkyl ester monomer, and the monomer having a carboxy group was measured by a method in accordance with ASTM D6866-20. The weight average molecular weights of the (meth)acrylic copolymers A-1 to A-11 were measured by the same method as the above-mentioned method for measuring the weight average molecular weight of the specific (meth)acrylic copolymer. The biomass ratio of each of the (meth)acrylic copolymers A-1 to A-11 was measured by a method in accordance with ASTM D6866-20.
[0113] Among the (meth)acrylic copolymers A-1 to A-11 obtained above, the (meth)acrylic copolymers A-1 to A-8 correspond to the specific (meth)acrylic copolymer in the present disclosure.
[0114] [Table 1]
[0115] Details of each monomer listed in Table 1 are as follows. <(A) Specific (meth)acrylic acid alkyl ester monomer> "LA": Lauryl acrylate [biomass content: 76.0%, manufactured by Kyoeisha Chemical Co., Ltd.] "LMA": Lauryl methacrylate [biomass content: 71.4%, manufactured by Kyoeisha Chemical Co., Ltd.] "SA": stearyl acrylate [biomass content: 81.7%, manufactured by Kyoeisha Chemical Co., Ltd.] <(B) Monomer Having a Hydroxyl Group> "2HEA": 2-hydroxyethyl acrylate (biomass content: 0%, manufactured by Osaka Organic Chemical Industry Co., Ltd.) <(C) Other (meth)acrylic acid alkyl ester monomers> "n-BA": n-butyl acrylate (biomass content: 0%, manufactured by Mitsubishi Chemical Corporation) <(D) Monomer having a carboxy group> "AA": acrylic acid (biomass content: 0%, manufactured by Osaka Organic Chemical Industry Co., Ltd.)
[0116] In Table 1, "-" in the monomer composition column means that the monomer in that column was not used.
[0117] [Preparation of Adhesive Composition] Example 1 217.4 parts by mass (100 parts by mass as solid content) of the (meth)acrylic copolymer A-1 solution, 1.11 parts by mass (0.5 parts by mass as solid content) of a crosslinking agent [product name: Coronate (registered trademark) L-45E, an adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), solid content concentration: 45% by mass, manufactured by Tosoh Corporation], and 10 parts by mass (10 parts by mass as solid content) of a tackifier resin [product name: SYLVALITE (registered trademark) 9000, softening point: 102°C, rosin ester resin, solid content concentration: 100% by mass, manufactured by Kraton] were thoroughly mixed to obtain a pressure-sensitive adhesive composition of Example 1.
[0118] [Examples 2 to 18] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 2, to obtain each of the adhesive compositions of Examples 2 to 18.
[0119] [Comparative Examples 1 to 7] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 3, to obtain each of the adhesive compositions of Comparative Examples 1 to 7.
[0120] The compositions (unit: mass %) and biomass ratios (unit: %) of the pressure-sensitive adhesive compositions of Examples 1 to 18 are shown in Table 2, and the compositions (unit: mass %) and biomass ratios (unit: %) of the pressure-sensitive adhesive compositions of Comparative Examples 1 to 7 are shown in Table 3.
[0121] The biomass degree of each of the pressure-sensitive adhesive compositions of Examples 1 to 18 and Comparative Examples 1 to 7 was measured by a method in accordance with ASTM D6866-20.
[0122] [Table 2]
[0123] [Table 3]
[0124] Details of the ingredients listed in Table 2 and / or Table 3 are as follows: <Tackifier resin> "S9000" [Product name: SYLVALITE (registered trademark) 9000, softening point: 102°C, rosin ester resin, solid content: 100% by mass, manufactured by Kraton] "PX1000" [Product name: YS Resin (registered trademark) PX1000, softening point: 100°C, polyterpene, solid content: 100% by mass, manufactured by Yasuhara Chemical Co., Ltd.] "T115" [Product name: YS Polystar (registered trademark) T115, softening point: 115°C, terpene phenol resin, solid content: 100% by mass, manufactured by Yasuhara Chemical Co., Ltd.] "T30" [Product name: YS Polyster (registered trademark) T30, softening point: 30°C, terpene phenol resin, solid content: 100% by mass, manufactured by Yasuhara Chemical Co., Ltd.]
[0125] <Crosslinking agent> "L-45E" (product name: Coronate (registered trademark) L-45, adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), solid content concentration: 45% by mass, manufactured by Tosoh Corporation) "D-110N" [Product name: Takenate (registered trademark) D-110N, adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP), solid content concentration: 75% by mass, manufactured by Mitsui Chemicals, Inc.]
[0126] In Tables 2 and 3, the values shown in the "blended amount" column are all values calculated as solid content. In Tables 2 and 3, "-" means that the ingredient in that column was not included.
[0127] [Preparation of adhesive sheets for evaluation] The adhesive composition prepared above was applied to the release-treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated to be easily peeled with a silicone-based release agent, so that the thickness after drying was 25 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C and a drying time of 2 minutes, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on one side of a polyethylene terephthalate (PET) film (trade name: Toyobo Ester (registered trademark) Film E5001, thickness: 25 μm, manufactured by Toyobo Co., Ltd.) (hereinafter simply referred to as "PET") as a substrate, and then left to stand for 7 days in an environment with an atmospheric temperature of 23 ° C and 50% RH to cure, and an evaluation adhesive sheet was prepared. The prepared pressure-sensitive adhesive sheet for evaluation had a laminated structure of release film / pressure-sensitive adhesive layer / substrate (PET).
[0128] [Measurement and Evaluation] 1. Stickiness (1) Substrate: Stainless steel plate The adhesive sheet for evaluation prepared above was cut into a size of 25 mm × 150 mm to prepare an adhesive sheet piece for evaluation. In addition, a stainless steel plate [SUS304 2B] with one side polished with sandpaper (roughness: #280) was prepared as an adherend. The release film was peeled off from the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET), and the surface of the adhesive layer exposed by the peeling was laminated on the polished surface of a stainless steel plate, and then a 2 kg roller was rolled back and forth once to press the surface, thereby preparing a test piece. The prepared test piece has a laminated structure of adherend (stainless steel plate) / evaluation adhesive sheet piece [adhesive layer / base material (PET)]. The prepared test piece was then left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH. After leaving the test piece still, the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was peeled off at 180° in the long side (150 mm) direction from the adherend (stainless steel plate) to measure the adhesive strength (unit: N / 25 mm) using a single column material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. The adhesiveness of the adhesive layer when the adherend was made of stainless steel (SUS) was then evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0129] -Evaluation criteria- A: The adhesive strength is 5.0N / 25mm or more. B: The adhesive strength is 3.0N / 25mm or more and less than 5.0N / 25mm. C: The adhesive strength is 2.0N / 25mm or more and less than 3.0N / 25mm. D: The adhesive strength is less than 2.0N / 25mm.
[0130] (2) Substrate: Polypropylene plate The pressure-sensitive adhesive sheet for evaluation prepared above was cut into pieces of 25 mm × 150 mm to prepare pressure-sensitive adhesive sheet pieces for evaluation. In addition, a polypropylene plate (product name: Kobe Polysheet PP-N-BN, manufactured by Showa Denko Materials Co., Ltd.) was prepared as an adherend. The release film was peeled off from the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET), and the surface of the adhesive layer exposed by the peeling was laminated on one side of a polypropylene plate, and then a 2 kg roller was rolled back and forth once to press the surface, thereby preparing a test piece. The prepared test piece has a laminated structure of adherend (polypropylene plate) / evaluation adhesive sheet piece [adhesive layer / base material (PET)]. The prepared test piece was then left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH. After leaving the test piece still, the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was peeled off at 180° in the long side (150 mm) direction from the adherend (polypropylene plate) to measure the adhesive strength (unit: N / 25 mm) using a single column type material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. The adhesiveness of the adhesive layer when the adherend material was polypropylene (PP) was then evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0131] -Evaluation criteria- A: The adhesive strength is 5.0N / 25mm or more. B: The adhesive strength is 3.0N / 25mm or more and less than 5.0N / 25mm. C: The adhesive strength is 2.0N / 25mm or more and less than 3.0N / 25mm. D: The adhesive strength is less than 2.0N / 25mm.
[0132] 2.Removability (1) Substrate: Stainless steel plate The adhesive sheet for evaluation prepared above was cut into a size of 25 mm × 150 mm to prepare an adhesive sheet piece for evaluation. In addition, a stainless steel plate [SUS304 2B] with one side polished with sandpaper (roughness: #280) was prepared as an adherend. The release film was peeled off from the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET), and the surface of the adhesive layer exposed by peeling was laminated on the polished surface of a stainless steel plate, and then a 2 kg roller was moved back and forth once to press the adhesive sheet piece to prepare a test piece. The prepared test piece has a laminated structure of adherend (stainless steel plate) / evaluation adhesive sheet piece [adhesive layer / base material (PET)]. Next, the prepared test piece was left to stand for 30 minutes in an environment with an atmospheric temperature of 23°C and 50% RH, and then left to stand for 168 hours in an environment with an atmospheric temperature of 60°C and 50% RH, and then left to stand for 30 minutes in an environment with an atmospheric temperature of 23°C and 50% RH. The adhesive strength (unit: N / 25 mm) of the test piece after standing when the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was peeled off at 180° in the long side (150 mm) direction from the adherend (stainless steel plate) was measured using a single column type material testing machine (model number: STA-1225) manufactured by A&D Co., Ltd. as a measuring device under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. In addition, the surface of the adherend (stainless steel plate) after peeling off the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was visually observed. Then, the removability of the adhesive layer when the material of the adherend was stainless steel (SUS) was evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0133] -Evaluation criteria- A: The adhesive strength is less than 8.0N / 25mm. B: The adhesive strength is 8.0N / 25mm or more and less than 10.0N / 25mm. C: The adhesive strength is 10.0 N / 25 mm or more and less than 12.0 N / 25 mm. D: The adhesive strength is 12.0 N / 25 mm or more, or glue residue is found on the surface of the stainless steel plate.
[0134] (2) Substrate: Polypropylene plate The pressure-sensitive adhesive sheet for evaluation prepared above was cut into pieces of 25 mm × 150 mm to prepare pressure-sensitive adhesive sheet pieces for evaluation. In addition, a polypropylene plate (product name: Kobe Polysheet PP-N-BN, manufactured by Showa Denko Materials Co., Ltd.) was prepared as an adherend. The release film was peeled off from the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET), and the surface of the adhesive layer exposed by the peeling was laminated on one side of a polypropylene plate, and then a 2 kg roller was rolled back and forth once to press the adhesive sheet piece to prepare a test piece. The prepared test piece has a laminated structure of adherend (polypropylene plate) / evaluation adhesive sheet piece [adhesive layer / base material (PET)]. Next, the prepared test piece was left to stand for 30 minutes in an environment with an atmospheric temperature of 23°C and 50% RH, and then left to stand for 168 hours in an environment with an atmospheric temperature of 60°C and 50% RH, and then left to stand for 30 minutes in an environment with an atmospheric temperature of 23°C and 50% RH. The adhesive strength (unit: N / 25 mm) of the test piece after standing was measured when the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was peeled off at 180° in the long side (150 mm) direction from the adherend (polypropylene plate) using a single column type material testing machine (model number: STA-1225) manufactured by A&D Co., Ltd. as a measuring device under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. In addition, the surface of the adherend (polypropylene plate) after peeling off the adhesive sheet piece for evaluation [structure: adhesive layer / base material (PET)] was visually observed. Then, the removability of the adhesive layer when the material of the adherend was polypropylene (PP) was evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0135] -Evaluation criteria- A: The adhesive strength is less than 8.0N / 25mm. B: The adhesive strength is 8.0N / 25mm or more and less than 10.0N / 25mm. C: The adhesive strength is 10.0 N / 25 mm or more and less than 12.0 N / 25 mm. D: The adhesive strength is 12.0 N / 25 mm or more, or glue residue is found on the surface of the polypropylene plate.
[0136] 3.Holding power (1) Substrate: Stainless steel plate The holding strength of the adhesive layer to the stainless steel plate was measured by a method in accordance with JIS Z 0237: 2009. Specifically, the measurement was performed as follows. The adhesive sheet for evaluation prepared above was cut into pieces of 25 mm × 90 mm to prepare adhesive sheet pieces for evaluation. In addition, a stainless steel plate [SUS304 2B] with one side polished with sandpaper (roughness: #280) was prepared as an adherend. A part of the release film of the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET) was peeled off, and the surface of the adhesive layer exposed by peeling was laminated on the polished surface of the stainless steel plate with an adhesion area of 25 mm x 25 mm, and then pressed with a 2 kg roller to prepare a test piece X1 in which a part of the adhesive layer of the evaluation adhesive sheet piece was attached to the stainless steel plate. Next, the prepared test piece X1 was left to stand for 30 minutes under an environment of an atmospheric temperature of 23 ° C and 50% RH to obtain a test piece X2. A static load of 1 kg was applied to the evaluation adhesive sheet piece attached to the stainless steel plate in the long side (90 mm) direction under an environment of an atmospheric temperature of 60 ° C, and after 60 minutes, the distance of displacement of the evaluation adhesive sheet piece from the stainless steel plate (i.e., the movement distance of the evaluation adhesive sheet piece) was measured. Then, the holding power of the adhesive layer when the material of the adherend was stainless steel (SUS) was evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0137] -Evaluation criteria- A: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is 0.01 mm or less. B: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is more than 0.01 mm and 0.05 mm or less. C: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is more than 0.05 mm and 0.10 mm or less. D: The moving distance of the evaluation pressure-sensitive adhesive sheet piece exceeds 0.10 mm.
[0138] (2) Substrate: Polypropylene plate The holding strength of the pressure-sensitive adhesive layer to the polypropylene plate was measured by a method in accordance with JIS Z 0237: 2009. Specifically, the measurement was performed as follows. The pressure-sensitive adhesive sheet for evaluation prepared above was cut into pieces measuring 25 mm × 90 mm to prepare pressure-sensitive adhesive sheet pieces for evaluation. In addition, a polypropylene plate (product name: Kobe Polysheet PP-N-BN, manufactured by Showa Denko Materials Co., Ltd.) was prepared as an adherend. A part of the release film of the evaluation adhesive sheet piece (composition: release film / adhesive layer / PET) was peeled off, and the surface of the adhesive layer exposed by peeling was laminated on the surface of a polypropylene plate with an adhesion area of 25 mm x 25 mm, and then pressed with a 2 kg roller to prepare a test piece Y1 in which a part of the adhesive layer of the evaluation adhesive sheet piece was attached to the polypropylene plate. Next, the prepared test piece Y1 was left to stand for 30 minutes under an environment of an atmospheric temperature of 23 ° C and 50% RH to obtain a test piece Y2. A static load of 1 kg was applied to the evaluation adhesive sheet piece attached to the polypropylene plate in the long side (90 mm) direction under an environment of an atmospheric temperature of 60 ° C, and after 60 minutes, the distance of displacement of the evaluation adhesive sheet piece from the polypropylene plate (i.e., the movement distance of the evaluation adhesive sheet piece) was measured. Then, the holding power of the adhesive layer when the material of the adherend is polypropylene (PP) was evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0139] -Evaluation criteria- A: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is 0.01 mm or less. B: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is more than 0.01 mm and 0.05 mm or less. C: The movement distance of the evaluation pressure-sensitive adhesive sheet piece is more than 0.05 mm and 0.10 mm or less. D: The moving distance of the evaluation pressure-sensitive adhesive sheet piece exceeds 0.10 mm.
[0140] [Table 4]
[0141] [Table 5]
[0142] As shown in Table 4, it was confirmed that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 18 exhibited good adhesion to both highly polar SUS and non-polar PP, and also had excellent removability. It was also confirmed that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 18 exhibited high holding power to both highly polar SUS and non-polar PP.
[0143] On the other hand, as shown in Table 5, it was confirmed that the adhesive layer formed from the adhesive composition of Comparative Example 1, in which the content of structural units derived from a specific (meth)acrylic acid alkyl ester monomer in the (meth)acrylic copolymer was less than 30 mass% relative to the total structural units, had inferior adhesion to non-polar PP compared to the adhesive layer formed from the adhesive composition of the Examples. It was confirmed that the adhesive layer formed by the adhesive composition of Comparative Example 2, in which the content of the tackifier resin was less than 10 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, had inferior adhesion to highly polar SUS and non-polar PP compared to the adhesive layer formed by the adhesive composition of the Example. It was also confirmed that the adhesive layer formed by the adhesive composition of Comparative Example 2 had inferior holding power to highly polar SUS and non-polar PP compared to the adhesive layer formed by the adhesive composition of the Example. It was confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 3, in which the content of the tackifier resin exceeds 60 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, has inferior removability to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was also confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 3 has inferior holding power to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was confirmed that the adhesive layer formed from the adhesive composition of Comparative Example 4, in which the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer exceeds 20 mass% relative to all structural units, has inferior adhesion to non-polar PP compared to the adhesive layers formed from the adhesive compositions of the Examples. It was confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 5, in which the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer is less than 5 mass% relative to all structural units, has inferior removability to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was also confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 5 has inferior holding power to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 6, in which the content of the crosslinking agent is less than 0.1 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, has inferior removability to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was also confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 6 has inferior holding power to highly polar SUS and non-polar PP compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was confirmed that the adhesive layer formed from the adhesive composition of Comparative Example 7, in which the content of crosslinking agent exceeded 2 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, had inferior adhesion to highly polar SUS and non-polar PP compared to the adhesive layers formed from the adhesive compositions of the Examples.
Claims
1. a (meth)acrylic copolymer containing 30% by mass to 95% by mass of structural units derived from a (meth)acrylic acid alkyl ester monomer having a biomass ratio of 70% or more, based on all structural units, and 5% by mass to 20% by mass of structural units derived from a monomer having a hydroxyl group, based on all structural units; a tackifier resin which is at least one selected from the group consisting of a terpene resin and a rosin resin; An isocyanate-based crosslinking agent; Including, the (meth)acrylic acid alkyl ester monomer having a biomass degree of 70% or more is at least one selected from the group consisting of lauryl acrylate, lauryl methacrylate, and stearyl acrylate; the monomer having a hydroxyl group is a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms, the content of the tackifier resin is 10 parts by mass to 60 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer, The pressure-sensitive adhesive composition has a content of the isocyanate-based crosslinking agent of 0.1 to 2 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer.
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the tackifier resin has a softening point of 80°C to 160°C.
3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the tackifier resin is 20 parts by mass to 45 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the (meth)acrylic copolymer does not contain a constituent unit derived from a monomer having a carboxy group, or the content of the constituent unit derived from a monomer having a carboxy group is in the range of more than 0 mass% to 1 mass% or less with respect to all constituent units.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein the content of structural units derived from a (meth)acrylic acid alkyl ester monomer having a biomass degree of 70% or more in the (meth)acrylic copolymer is 4 times or more, by mass, the content of structural units derived from the monomer having a hydroxyl group.
6. The pressure-sensitive adhesive composition according to any one of claims 1 to 5, wherein the (meth)acrylic copolymer has a biomass ratio of 40% or more.
7. A substrate; a pressure-sensitive adhesive layer provided on the substrate and formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 6; An adhesive sheet comprising:
Citation Information
Patent Citations
Fine particle pressure-sensitive adhesive composition
JP2011508804A
Adhesive composition and adhesive film
JP2016190902A
Adhesive composition and adhesive sheet
JP2019142997A
Adhesive tape and article
JP2020041023A
Adhesive composition
JP2020105308A
